The STEM Dilemma Skills that Matter to Regions - Stewart, Fran (W.E. Upjohn Institute, 2017)
Stewart confront several key issues facing policymakers and educators, including the role of public investment in human capital, the types of human capital investment that provide the greatest public return, and whether those investments should vary by region. She shows that not all high-paying jobs require STEM skills; that not all good-paying, highly skilled STEM jobs require college degrees; and that "soft skills" are important for STEM as well as other high-paying jobs.